(untitled) (Journal of the College of Basic Education, 2023)
The research aims to identify the concept of medium-sized industries and their relationship to small industries and to identify the nature of the spatial distribution of medium-sized industries in Baghdad Governorate and by districts for the year 2021 As well as getting acquainted with the industrial structure of this industry. - The research assumes that the Baghdad governorate possesses huge potentials that are not invested in industrial activity due to several problems related to industry and development. Also, there is a large discrepancy in the distribution of medium-sized industries at the level of the issue of Baghdad Governorate for the year 2021. As for the research methodology, the research dealt with the following topics: the concept of medium-sized industries and their characteristics, the structure of medium-sized industries in Baghdad Governorate for the year 2021, as well as conclusions and recommendations. The research concluded that the total medium-sized industries in Baghdad Governorate for the year 2021 amounted to 39 factories, in which 712 workers worked, and the value of wages amounted to 5,355,941 thousand dinars, while the value of sales was 36,595,223 thousand dinars, while the value of production requirements was 16,739,315 in one thousand dinars. As for the most important recommendations, they were represented by 1- Raising awareness of the importance of medium enterprises and clarifying their role in economic development 2- Commercial banks and financial institutions must keep pace with the current economic situation, participate in financing economic and social development plans, and face the challenges they face.